2010
DOI: 10.1016/j.niox.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical translation of nitrite therapy for cardiovascular diseases

Abstract: The anion nitrite is an oxidative breakdown product of nitric oxide (NO) that has traditionally been viewed as a diagnostic marker of NO formation in biological systems. In this regard, nitrite has long been considered an inert oxidation product of NO metabolism. More recently, this view has changed with the discovery that nitrite represents a physiologically relevant storage reservoir of NO in blood and tissues that can readily be reduced to NO under pathological conditions. This has sparked a renewed interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 80 publications
(98 reference statements)
1
53
0
3
Order By: Relevance
“…20, 21 The expression and phosphorylation of Akt and eNOS in ischemic adductor muscles of WT mice and non-ischemic adductor muscles of sham mice were assessed by Western blot analysis on postoperative day 3. DATS administration did not alter the phosphorylation of Akt at Thr-308 Figure 2.…”
Section: Enos Activation Is Essential For Dats-induced Revascularizatmentioning
confidence: 99%
See 1 more Smart Citation
“…20, 21 The expression and phosphorylation of Akt and eNOS in ischemic adductor muscles of WT mice and non-ischemic adductor muscles of sham mice were assessed by Western blot analysis on postoperative day 3. DATS administration did not alter the phosphorylation of Akt at Thr-308 Figure 2.…”
Section: Enos Activation Is Essential For Dats-induced Revascularizatmentioning
confidence: 99%
“…2 The production of H2S is attributed to 3 endogenous enzymes: cystathionine γ -lyase (CGL or CSE), cystathionine β-synthase (CBS), and 3-mercaptopyruvate sulfurtransferase (3MST). 3-5 Recently, it was reported that H2S possesses antioxidant, anti-apoptotic, anti-inflammatory, and mitochondrial-protecting activities in various cell DATS Augments Ischemia-Induced Angiogenesis Histology Ischemic muscles of mice treated with the vehicle control or DATS were collected at postoperative day 21. Frozen sections of 6-μm thickness were prepared using a cryostat (Leica CM3050 S, Leica Biosystems) and stained with an anti-CD31 antibody (Becton Dickinson) to detect capillary ECs.…”
mentioning
confidence: 99%
“…Exogenous sources, principally environmental pollutants and intake of vegetables, also contribute to this NO reserve. While the anion NO 2 Ϫ has traditionally been considered a mere oxidative breakdown product of NO and a diagnostic marker of its formation at nanomolar concentrations in biological systems, more recent discoveries indicate that NO 2 Ϫ represents a physiologically relevant storage reservoir of NO in blood and tissues with distinct signaling functions at nearphysiological concentrations (19). The NO 2 Ϫ anion can be readily reduced to bioactive NO along a physiological oxygen and pH gradient either nonenzymatically (167) or by a number of enzymes, including XORs, NOS, mitochondrial cytochromes, and deoxygenated hemoglobin and myoglobin (25,71,72,122,140).…”
Section: No Donorsmentioning
confidence: 99%
“…However, the major concern of such a strategy remains the potential risk of inadvertent systemic vasodilation and hypotension caused by circulating NO 2 Ϫ reductases. Currently, there are several clinical studies underway to investigate safety, i.e., methemoglobin formation and inadvertent hypotension, and potential therapeutic efficacy of NO 2 Ϫ administration in patients with acute myocardial infarction, cerebral vasospasm, and pulmonary hypertension (19). When NO 2 Ϫ is administered during noninflammatory states, one of the mechanisms thought to mediate the beneficial effects is that nitrites are stored in erytrocytes and can be secondarily reduced to vasoactive NO by, e.g., XORs under anaerobic conditions (10).…”
Section: No Donorsmentioning
confidence: 99%
“…In addition, experimental studies have shown that enhancing NO levels through genetic manipulation leads to improved survival,12 decreased remodeling,16 and improved cardiac function following ischemia‐induced HF in mice. Among NO donors, sodium nitrite (NaNO 2 ) represents a promising therapeutic agent for the treatment of HF,17 being an attractive candidate for restoring physiological NO signaling in states of chronic NO insufficiency such as myocardial ischemia. NaNO 2 is rapidly absorbed from the circulation by peripheral tissues and stored in cells until conversion to NO is needed 18, 19, 20.…”
Section: Introductionmentioning
confidence: 99%